Identity-Based Encryption for Preserving Privacy In Cloud For Publish/Subscribe System (International Journal of Engineering and Computer Science, 2015)
The provisioning of basic security mechanism such as authentication andconfidentiality in the publish/subscribe system. Authentication in this system is difficult to achievedue to the loose coupling between publishers and subscribers. Likewise, Confidentiality of eventsand subscriptions conflicts with content-based routing. To ensure authentication and confidentialityin broker less publish/subscribe system we adopt pairing based cryptography mechanism. Furtherly,broadcasting encryption algorithm is adapted to provide subscription confidentiality by clusteringsubscribers according to their subscription by providing a private key with their credentials. Soweadapt identity based encryption for providing private key to the subscribers with their credentialsbased on their identity (e.g. e-mail). This technique enables efficient routing of encrypted events,provides thorough analysis of various attacks on subscription confidentiality and a fine grained keymanagement. Moreover, the evaluations show that providing security is affordable w.r.t. 1)throughput of the proposed cryptographic primitives, and 2) delays incurred during theconstruction of the publish/subscribe overlay and the event dissemination.